Perancangan Aplikasi Ukumulasi Tentatif Pimpinan PROKOPIM Bebasis Web - Nur Sopiana Laili (Pusat Riset dan Inovasi Nasional, 2023)
At the prokopim office of the Regional Secretariat of Central Lombok Regency, incoming letters are still stored in files that are still manual in nature, so that it is possible for these letters to be scattered and when looking for the desired letter you have to search for it one by one, and it will take a long time in the search process. The methodology used in making this system is a data collection method in the form of observation, interviews and literature study, while the analytical method used is PIECES analysis, for the design method using the System Development Life Cycle (SDLC). Based on the results of the research that the mail archiving application can accommodate the storage process becomes more effective, so that the search for incoming and outgoing letters is faster, the system can back up data, so that it can minimize damage or loss of data making incoming and outgoing mail reports as needed, so Facilitate reporting to superiors.